INCIDENTAL BONE METASTASIS FINDING FROM CT SIMULATION FOR BREAST CANCER RADIOTHERAPY - Nugroho, Rafiq Sulistyo; Amalia, Fini; Bayhaqi Nashir Aslam, Achmad; Petrarizky, Alfred Julius (International Journal of Radiology and Imaging, 2024)
Breast cancer has the highest tendency for bone metastasis. This study aimed to evaluate bone metastasis using computed tomography (CT) simulation for breast cancer radiotherapy. We retrospectively reviewed the patient's CT images from September 2022 to February 2023. The median age was 48 (34–80), and almost half of the patients had T3-4 and N2-3 disease. Nine out of 53 patients (17%) had bone metastasis, and 8 had multiple lesions. The vertebral spine was the predominant site of bone metastasis. Due to the high rate of bone spreading, bone evaluation is mandatory during CT simulation for more appropriate treatment. Keywords: Bone metastasis, computed tomography, breast cancer